ABBA : An Agent-Based Model of the Banking System - Chan-Lau, Jorge (IMF Working Papers; Working Paper, 2017)
A thorough analysis of risks in the banking system requires incorporating banks' inherent heterogeneity and adaptive behavior in response to shocks and changes in business conditions and the regulatory environment. ABBA is an agent-based model for analyzing risks in the banking system in which banks' business decisions drive the endogenous formation of interbank networks. ABBA allows for a rich menu of banks' decisions, contingent on banks' balance sheet and capital position, including dividend payment rules, credit expansion, and dynamic balance sheet adjustment via risk-weight optimization. The platform serves to illustrate the effect of changes on regulatory requirements on solvency, liquidity, and interconnectedness risk. It could also constitute a basic building block for further development of large, bottom-up agent-based macro-financial models.